Detailed Patterns of Methane Distribution in the German Bight - Bussmann, Ingeborg; Brix, Holger; Flöser, Götz; Ködel, Uta; Fischer, Philipp (Frontiers in Marine Science, 2021)
Although methane is a widely studied greenhouse gas, uncertainties remain with respect to the factors controlling its distribution and diffusive flux into the atmosphere, especially in highly dynamic coastal waters. In the southern North Sea, the Elbe and Weser rivers are two major tributaries contributing to the overall methane budget of the southern German Bight. In June 2019, we continuously measured methane and basic hydrographic parameters at a high temporal and spatial resolution (one measurement per minute every 200–300 m) on a transect between Cuxhaven and Helgoland. These measurements revealed that the overall driver of the coastal methane distribution is the dilution of riverine methane-rich water with methane-poor marine water. For both the Elbe and Weser, we determined an input concentration of 40–50 nmol/L compared to only 5 nmol/L in the marine area. Accordingly, we observed a comparatively steady dilution pattern of methane concentration toward the marine realm. Moreover, small-scale anomalous patterns with unexpectedly higher dissolved methane concentrations were discovered at certain sites and times. These patterns were associated with the highly significant correlations of methane with oxygen or turbidity. However, these local anomalies were not consistent over time (days, months). The calculated diffusive methane flux from the water into the atmosphere revealed local values approximately 3.5 times higher than background values (median of 36 and 128 μmol m–2 d–1). We evaluate that this occurred because of a combination of increasing wind speed and increasing methane concentration at those times and locations. Hence, our results demonstrate that improved temporal and spatial resolution of methane measurements can provide a more accurate estimation and, consequently, a more functional understanding of the temporal and spatial dynamics of the coastal methane flux.